High‐dose chemotherapy in relapsed or refractory Hodgkin lymphoma patients: a reappraisal of prognostic factors1. Issue 1 (30th March 2012) - Cocorocchio, E; Peccatori, F; Vanazzi, A; Piperno, G; Calabrese, L; Botteri, E; Travaini, L; Preda, L; Martinelli, G
Abstract High‐dose chemotherapy (HDCT) has a consolidated role in the treatment of patients with refractory or relapsed Hodgkin lymphoma (HL). We report clinical results of 97 HL patients who underwent HDCT for refractory (62 patients) or relapsed (35 patients) diseases in Istituto Europeo di Oncologia, from 1995 to 2009. Treatment included high‐dose carmustine, etoposide, cytarabine and melphalan in 84 patients and high‐dose idarubicin and melphalan in 13 patients with subsequent peripheral hemopoietic stem cells transplant. Outcomes were evaluated in terms of progression‐free survival (PFS) and overall survival (OS). In order to identify prognostic factors for outcome, a multivariate analysis for age, sex, disease status (refractory/relapsed), disease stage, B symptoms, presence of extranodal involvement, bulky disease, elevated lactate dehydrogenase, number of previous chemotherapy lines, remission status before transplant, 18F‐fluoro‐deoxy‐d‐glucose positron emission tomography (18FDG‐PET) status before and after transplant was done. A clinical response was achieved in 91% of patients, with complete remissions in 76/97 patients. With a median follow‐up of 45 months (range 1–164 months), 5‐year PFS and OS were 64% and 71%, respectively. Remission status after induction therapy, 18F‐fluoro‐deoxy‐d‐glucose positron emission tomography status before and after transplant were the most important prognostic factors for PFS and OS in univariate or multivariate analyses. HDCT is able to induce a high remission rate and a prolonged PFS in more than 50% of the patients with refractory and relapsed HL. Copyright © 2012 John Wiley & Sons, Ltd.